2006
DOI: 10.1002/uog.2839
|View full text |Cite
|
Sign up to set email alerts
|

Cord insertion into the lower third of the uterus in the first trimester is associated with placental and umbilical cord abnormalities

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 17 publications
3
70
0
Order By: Relevance
“…Because vasa previa is rare, to evaluate the usefulness of screening for vasa previa, a large number of subjects is required. In this paper we present a continuation of our previous study 15 with sufficient case numbers to demonstrate associations between low cord insertion at the first trimester and vasa previa.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Because vasa previa is rare, to evaluate the usefulness of screening for vasa previa, a large number of subjects is required. In this paper we present a continuation of our previous study 15 with sufficient case numbers to demonstrate associations between low cord insertion at the first trimester and vasa previa.…”
Section: Introductionmentioning
confidence: 75%
“…Recently, ultrasonographic assessments have become popular to detect aneuploidy and other fetal anomalies in the first trimester. In a previous study, we demonstrated that an umbilical cord insertion site located on the lower third of the uterine wall at the first trimester was associated with various placental abnormalities at delivery, including a low‐lying placenta and velamentous cord insertion 14,15 . We concluded that the systematic identification of the cord insertion site during pregnancy while testing for other fetal abnormalities may be useful for the identification of vasa previa.…”
Section: Introductionmentioning
confidence: 86%
“…Our findings indicate that abnormal cord insertion onto the placenta is associated with an increased rate of CHD compared to centrally or paracentrally attached cords. Cord insertion is routinely evaluated during anatomy screening sonography and has been associated with placental and umbilical cord anomalies . The cardiac defects most strongly associated with abnormal cord insertion were conotruncal defects, left heart disease, and right heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of Type II vasa previa may be explained by atrophy of the partial placenta around cervical os due to a poor blood supply. In our study, regardless of the location of placenta at delivery, low-lying placentas, velamentous cord insertion and placental abnormalities occurred frequently in cases in which cord insertion was noted to be in the lower uterine segment during the first trimester [11] . The cord insertion site is important for placental development.…”
Section: Discussionmentioning
confidence: 92%